POSITIVE POLITENESS STRATEGIES REFLECTED IN ANAK SASADA MOVIE - Destin Merry Desta; I Wayan Dirgeyasa; Lidiman Sahat Martua Sinaga (LINGUISTICA, 2019)
This research was focused on the topic about positive politeness strategies reflected in Anak Sasada movie. This study was aimed to describe the types of positive politeness stategies employed by the characters in Anak Sasada movie. To describe the positive politeness strategies realized in the utterances employed by the characters in Anak Sasada movie. This study was conducted by descriptive qualitative method. The source of data was taken from Anak Sasada script movie. The data was collected by using documentary sheet. The technique for analyzing the data is descriptive qualitative research.The results of the study show the important points. There are ten types of positive politeness strategies employed by the characters in Anak Sasada movie when having conversation: Among all strategies, Notice is the most frequent strategy as the characters need to share notice with the others. Notice strategies (16 out of 77), Use Solidarity in Group Identity Markers (15), Offer or promise (3), Exaggerate (approval, sympathy with hearer) (6),  Joke (5 out of 77), Assert or Presupposes Speaker’s Knowledge Aggreement (1), Give (Ask for) Reasons (11 out 77), Give gifts to Addressee (goods, symphaty, understanding, cooperation) (8 out of 77). Keywords : Politeness , Toba Batak, Positive Politeness